Protein Adsorption on a Laser-Modified Titanium Implant Surface. Issue 2 (April 2015) - Cei, Silvia; Karapetsa, Dimitra; Aleo, Emanuela; Graziani, Filippo
Abstract : Purpose: The aim of this study was to investigate the earlier phase of the osseointegration of a laser-treated implant surface in terms of human protein adsorption. Materials and Methods: Titanium surfaces were divided into machined (M), sandblasted (SB), and laser-treated (LT). The LT surfaces were created with an Nd diode-pumped laser in Q-switching, whereas the SB were treated with Al2 O3 . An x-ray photoelectron spectroscopy (XPS) analysis of titanium surface was performed. Titanium discs were used for albumin and fibronectin adsorption evaluation through fluorescence intensity. Fibronectin evaluation was also made with Western Blot analysis on experimental implants. Results: LT discs appeared to trigger a higher albumin and fibronectin adsorption with a regular pattern. The mean count of albumin adsorption was 0.29 and 3.8 for SB and LT, respectively ( P = 0.016), whereas fibronectin values were 0.67 and 4.9 for (SB) and (LT) titanium ( P = 0.02). XPS analysis showed that titanium, oxygen, carbon, and nitrogen were found on all 3 surfaces. Conclusion: Laser-engineered porous titanium surface seems to promote, in vitro, the adsorption of albumin and fibronectin more than sandblasted (SB) or machined (M) implants.